Interview 2 - Abubakari, Yushawu
This file contains the interview notes with Manuka. Manuka (Pseudonymize) is 33 years and live along in his house. He has 12 siblings from a polygamous home. Manuka is a leader who have other scammers working under him at the local level. But Manuka is involved in international cooperation with scammers in Nigeria, USA, and Canada. The interview was conducted at Manuka’s residence. The interview was not recorded, therefore, the script is based on notes taken during the interview session.